Theory of Teaching Skills in Pedagogy - Rajabova Munisxon (Peerian Journals Publishing, 2022)
If the pedagogy professional skill program is considered practical, then the priority will be its integral quality – the teacher's skill. Despite the fact that there are so many definitions given to pedagogical skills, some aspects of skill are certainly expressed in them. In this article, feedback and feedback will be made about the skills that teachers need to master and their use in the process of narrowly giving.
Keywords: pedagogy; skill; communicative skill